Keberagaman Tenaga Kerja dan Budaya Organisasi Pada Proyek Konstruksi Jalan Nasional - Susilo Catur Mulyawuri; Rina Hermawati; Rini S. Soemarwoto (Jayapangus Press, 2026)
Workforce diversity is an inherent characteristic of large-scale construction projects involving employees from diverse cultural backgrounds. This study aims to examine workforce diversity management in the Simpang Perdau–Batu Ampar Permanent Replacement Road Project in East Kutai Regency through the lens of organizational anthropology. A qualitative approach was employed using observation, in-depth interviews and questionnaires involving 18 informants comprising project management, local employees and non-local employees. The findings indicate that competency-based recruitment has created a multicultural work environment without using ethnic identity as a selection criterion. Organizational culture serves as a mechanism for social integration through professionalism, open communication, teamwork and a sense of belonging. Workforce diversity does not develop into ethnic conflict because organizational identity is more dominant than cultural group identity. Instead, diversity enhances team productivity by fostering the exchange of knowledge, experience, creativity and collaboration. These findings demonstrate that organizational culture effectively manages diversity as a form of social capital that promotes workplace harmony and improves organizational performance.